A generic TG‐186 shielded applicator for commissioning model‐based dose calculation algorithms for high‐dose‐rate 192Ir brachytherapy. Issue 11 (19th October 2017) - Ma, Yunzhi; Vijande, Javier; Ballester, Facundo; Tedgren, Åsa Carlsson; Granero, Domingo; Haworth, Annette; Mourtada, Firas; Fonseca, Gabriel Paiva; Zourari, Kyveli; Papagiannis, Panagiotis; Rivard, Mark J.; Siebert, Frank−André; et al.
Abstract : Purpose: A joint working group was created by the American Association of Physicists in Medicine (AAPM), the European Society for Radiotherapy and Oncology (ESTRO), and the Australasian Brachytherapy Group (ABG) with the charge, among others, to develop a set of well‐defined test case plans and perform calculations and comparisons with model‐based dose calculation algorithms (MBDCAs). Its main goal is to facilitate a smooth transition from the AAPM Task Group No. 43 (TG‐43) dose calculation formalism, widely being used in clinical practice for brachytherapy, to the one proposed by Task Group No. 186 (TG‐186) for MBDCAs. To do so, in this work a hypothetical, generic high‐dose rate (HDR) 192 Ir shielded applicator has been designed and benchmarked. Methods: A generic HDR 192 Ir shielded applicator was designed based on three commercially available gynecological applicators as well as a virtual cubic water phantom that can be imported into any DICOM‐RT compatible treatment planning system (TPS). The absorbed dose distribution around the applicator with the TG‐186 192 Ir source located at one dwell position at its center was computed using two commercial TPSs incorporating MBDCAs (Oncentra ® Brachy with Advanced Collapsed‐cone Engine, ACE™, and BrachyVision ACUROS™) and state‐of‐the‐art Monte Carlo (MC) codes, including ALGEBRA, BrachyDose, egs_brachy, Geant4, MCNP6, and Penelope2008. TPS‐based volumetric dose distributions for the previously reported "source centered in water" and "source displaced" test cases, and the new "source centered in applicator" test case, were analyzed here using the MCNP6 dose distribution as a reference. Volumetric dose comparisons of TPS results against results for the other MC codes were also performed. Distributions of local and global dose difference ratios are reported. Results: The local dose differences among MC codes are comparable to the statistical uncertainties of the reference datasets for the "source centered in water" and "source displaced" test cases and for the clinically relevant part of the unshielded volume in the "source centered in applicator" case. Larger local differences appear in the shielded volume or at large distances. Considering clinically relevant regions, global dose differences are smaller than the local ones. The most disadvantageous case for the MBDCAs is the one including the shielded applicator. In this case, ACUROS agrees with MC within [−4.2%, +4.2%] for the majority of voxels (95%) while presenting dose differences within [−0.12%, +0.12%] of the dose at a clinically relevant reference point. For ACE, 95% of the total volume presents differences with respect to MC in the range [−1.7%, +0.4%] of the dose at the reference point. Conclusions: The combination of the generic source and generic shielded applicator, together with the previously developed test cases and reference datasets (available in the Brachytherapy Source Registry), lay a solid foundation in supporting uniform commissioning procedures and direct comparisons among treatment planning systems for HDR 192 Ir brachytherapy.